Dual-actuator servo system design for fast data rate and high density hard disk drives - Zheng, Jinchuan (2008)
The dual-actuator structure has intrinsic property to meet fast data rate and high throughput requirements in hard disk drives (HDDs). In order to sustain the continuing increase of track density, the dual-actuator servo system needs to be developed for more precise head positioning accuracy in the presence of the disturbances and the interactions between the actuators. In this thesis, control structures and controller design methods are developed for the dual-actuator control system to compensate for the interactions as well as the other disturbance sources.